PEMBELAJARAN BERBASIS PROYEK PERMAINAN TRADISIONAL LAYANG-LAYANG DALAM PEMBELAJARAN SBDP UNTUK MENUMBUHKAN DIMENSI KREATIVITAS DI SD 6 KANDANGMAS KUDUS - Riska Kumala Fitri; Lintang Matumona; Oktafani Aulia; Vina Auliyatul Khasanah; Elya Umi Hanik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the application of project-based learning through traditional kite-making activities to foster creativity in fourth-grade students in Arts and Culture (SBdP) at SD 6 Kandangmas. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation to understand the learning process and the development of students' creativity. The results showed that the integration of kite-making into the project-based learning model provided meaningful opportunities for students to explore ideas, demonstrate originality, refine designs, and solve problems creatively. Students also demonstrated high levels of engagement and collaboration, along with improved communication skills, responsibility, and independence during the project implementation. This activity provided a contextual and culturally aligned learning experience, thus strengthening students' appreciation of local traditions while developing their creative competencies. This study concluded that traditional games can be an effective and enjoyable learning medium in Arts and Culture (SBdP), especially in elementary schools without dedicated art teachers. Further research is recommended to examine the impact of this model on other competencies and in more diverse school contexts.